Betaine and Beet Molasses Enhance L-Lactic Acid Production by Bacillus coagulans - Xu, Ke (Public Library of Science, 2014)

(untitled)
Lactic acid is an important chemical with various industrial applications, and it can be efficiently produced by fermentation, in which Bacillus coagulans strains present excellent performance. Betaine can promote lactic acid fermentation as an effective osmoprotectant. Here, positive effect of betaine on fermentation by B. coagulans is revealed. Betaine could enhance lactic acid production by protecting l-LDH activity and cell growth from osmotic inhibition, especially under high glucose concentrations and with poor organic nitrogen nutrients. The fermentation with 0.05 g/L betaine could produce 17.9% more lactic acid compared to the fermentation without betaine. Beet molasses, which is rich in sucrose and betaine, was utilized in a co-feeding fermentation and raised the productivity by 22%. The efficient lactic acid fermentation by B. coagulans is thus developed by using betaine and beet molasses.